Model Pemberdayaan Ekonomi Masyarakat Nagari Melalui Pariwisata dan Seni Budaya berbasis Local Wisdom - Rahmadya, Budi; Maruf, Maruf; Nursyam, Yesriva; Putri, Rahmi Eka (Universitas Negeri Padang, 2025)
The research objective is to analyze the local wisdom-based community economic empowerment model in Nagari Matua Hilia, especially in the tourism sector. This research explores the extent to which the tourism sector contributes to community income and identifies their expectations of universities and the government in fostering tourism development. The method used is descriptive research with a quantitative approach by providing questionnaires to tourism businesses in the region. The results show that some communities have attended tourism business management training, while others have not had access to such training. The majority of available training is organized by the government, with limited involvement from universities and private institutions. In addition, the average income from the tourism business is around 3 million rupiah per month, which still has the potential to be increased. To strengthen local wisdom-based economic empowerment, more comprehensive and sustainable training is needed, including digital marketing strategies, financial management, and local culture-based tourism product innovation. In addition, increased income can be encouraged through the development of more attractive tourist attractions, utilization of digital technology in promotion, and cooperation with various parties. An empowerment model based on local wisdom can be an effective strategy in optimizing the economic potential of the community and making tourism a leading sector in Nagari Matua Hilia.